The Clinical Significance and Application of Vascular Stiffness Measurements - Boutouyrie, Pierre; Bruno, Rosa-Maria (American journal of hypertension, 2019)
Increasing evidence points out at vascular stiffness (and in particular aortic stiffness measured by pulse wave velocity) as a reliable biomarker of vascular aging, able to integrate in a single measure the overall burden of cardiovascular (CV) risk factors on the vasculature over time; furthermore, it may be per se a mechanism of disease, by inducing microcirculatory damage and favoring CV events. Increased aortic stiffness has been shown to predict future CV events and improve risk reclassification in those at intermediate risk. However, several questions in this field are still open, limiting the wide use of these tools in the clinical practice. This article will review the basic aspects of physiology of large artery stiffness, as well as current evidence about its possible clinical applications.